A New, One-Pot, Multicomponent Synthesis of Bioactive N -Pyrazolylformamidines under Microwave Irradiation - Lim, F.; Luna, G.; Dolzhenko, Anton (Georg Thieme Verlag, 2016)
A one-pot, three-component, microwave-assisted reaction of polysubstituted 5-aminopyrazoles, triethyl orthoformate, and a series of cyclic secondary amines was developed and successfully employed for the synthesis of novel N-pyrazolylformamidines. Under catalyst-free conditions, the reaction proceeded in a chemo- and regioselective manner, resulting in the formation of unsymmetric formamidines, which were isolated in high yields and purity. Some of the prepared compounds were found to inhibit interleukin-17 secretion in phenotypic in vitro assays.